2017
DOI: 10.1016/j.sjpain.2017.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Pain catastrophizing, perceived injustice, and pain intensity impair life satisfaction through differential patterns of physical and psychological disruption

Abstract: AbstractBackground and purposePrevious research has highlighted the importance of cognitive appraisal processes in determining the nature and effectiveness of coping with chronic pain. Two of the key variables implicated in appraisal of pain are catastrophizing and perceived injustice, which exacerbate the severity of pain-related distress and increase the risk of long-term disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 56 publications
(55 reference statements)
6
17
0
Order By: Relevance
“…However, even after accounting for these effects, higher pain-related injustice appraisals were still associated with worse pain-related functioning, hence attesting to their unique explanatory value. Furthermore, aligning with previous research in children (Miller et al, 2016) and adults (Sturgeon et al, 2017;Sullivan et al, 2008;Yakobov et al, 2014), our findings indicated that despite strong correlations between injustice appraisals and pain catastrophizing (r range [0.58, 0.72], ps < .01), injustice appraisals were still associated with pain-related functioning after controlling for pain-related catastrophizing, hence suggesting that pain-related injustice appraisals are distinct from catastrophic appraisals about pain and constitute an important target for intervention. Furthermore, while the effects of injustice appraisals were stronger in the clinical sample, comparable findings were observed in the school sample.…”
Section: Discussionsupporting
confidence: 89%
“…However, even after accounting for these effects, higher pain-related injustice appraisals were still associated with worse pain-related functioning, hence attesting to their unique explanatory value. Furthermore, aligning with previous research in children (Miller et al, 2016) and adults (Sturgeon et al, 2017;Sullivan et al, 2008;Yakobov et al, 2014), our findings indicated that despite strong correlations between injustice appraisals and pain catastrophizing (r range [0.58, 0.72], ps < .01), injustice appraisals were still associated with pain-related functioning after controlling for pain-related catastrophizing, hence suggesting that pain-related injustice appraisals are distinct from catastrophic appraisals about pain and constitute an important target for intervention. Furthermore, while the effects of injustice appraisals were stronger in the clinical sample, comparable findings were observed in the school sample.…”
Section: Discussionsupporting
confidence: 89%
“…Our results indicated a strong correlation between scores on the Daily IEQ and Daily PCS; this finding is not surprising and echoes prior findings suggesting a considerable degree of overlap between these constructs (Sturgeon et al., 2017; Sullivan et al., 2008). It is notable that, despite high correlations between these variables at both the individual cluster and daily level, there was a weaker correlation between Daily IEQ and PCS scores at the daily level (approximately 55% shared variance, compared to 72.7% shared variance at the individual cluster level).…”
Section: Discussionsupporting
confidence: 89%
“…There are predictable patterns of negative cognitive appraisal that can develop out of a complex and often treatment‐resistant medical condition such as chronic pain. For example, individuals who endorse a stronger belief that their pain symptoms reflect a catastrophic personal experience are vulnerable to a greater degree of symptom intensity and burden (Edwards et al., 2011; Scott et al., 2014; Sturgeon et al., 2017; Sullivan et al., 2001; Westman et al., 2011) and show impaired recovery across time (Scott et al., 2014; Sullivan et al, 2011; Westman et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As the fully specified models were fully saturated, model fit indices indicated perfect fit and are therefore not reported. Given the strong theoretical relationship between pain catastrophizing and perceived injustice, 56,58 these factors were freed to covary in all fully specified models.…”
Section: Analysesmentioning
confidence: 99%